Differences in The Effect of Quantum Learning Methods with Mind Mapping and Jigsaw Methods on Students with Different Levels of Creativity Against - ., Hariyanto; Maghfiroh, Nasruliyah Hikmatul (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2023)
This study aims to find out the differences in the effect of the quantum learning model with the mind map method and the Jigsaw cooperative learning model on students with various levels of creativity. The subjects of this study were students of class X IPA 1 at SMAN I Subob - Situbondo and class X IPA 1 at SMAN 1 Besuki - Situbondo. This research is an experimental research. Data collection techniques through tests and observations. Data were analyzed using Two Way ANOVA. The results of the data analysis show that: (1) The learning outcomes of students who have high creativity are better than the learning outcomes of students with low creativity, (2) The learning outcomes of students with high creativity are better in quantum teaching learning with the mind mapping method than with the Jigsaw method, (3) There is a positive interaction between student creativity and learning models on student learning outcomes.